Automotive engine fault diagnosis using acoustic emission technique - Nur Naquiah, Mohammad Ali (2010)
This thesis was carried out to diagnose faults in an automotive engine using acoustic emission method. Proton Persona’s engine, which is a four cylinder engine, powered by 1.6 liters double overhead camshaft (DOHC) with two different locations (Point A and Point B) marked was used as the main test-rig. There were three tests conducted for this project, the pencil-break test, engine under idle condition and engine under fuel injector shut off condition. Pencil-break test is performed in order to check the most suitable material to be used as medium to transfer the signals. The source of the Acoustic Emission (AE) signals was from the condition where the fuel injector was shut off when the engine is running, and it was captured using AE sensor with the help from Physical Acoustic AE-win 3.1 software. For engine under idle and shut off condition, all the domain parameters (RMS amplitude, peak amplitude and energy) was processed using MATLAB software. The parameters were then compared between idle and shut off condition for each fuel injector shut off. The results shows that the different of AE parameters between Point A and Point B, where Point B shows higher value than Point A in idle condition and also under fuel injector shut off condition. During shut off condition, the RMS amplitude, peak amplitude and energy produced higher energy level compare to idle condition. This indicates defects or faults occurred. In addition, Pekan number, X was introduced as the indicator or ratio of value before fuel injector shut off to value during fuel injector shut off.